Failure mechanism of underwater shield tunnel: An experimental and theoretical study. (July 2023) - Liang, Kun; Feng, Kun; Zhang, Li; He, Chuan; Su, Ang; Guo, Wenqi
Highlights: Plastic hinge-based approach was proposed to investigate the failure mechanism of underwater shield tunnel. The formation and failure index of joint plastic hinge and segmental plastic hinge were defined. Failure mechanism of straight-joint assembly structure and staggered-joint assembly structure was revealed. Abstract: This study proposes a plastic hinge-based approach to investigate the failure mechanism of underwater shield tunnel lining structures. Joint plastic hinge and segmental plastic hinge are defined based on the observed failure patterns. The rotational demands of the plastic hinges are obtained through theoretical and numerical methods, and the locations of potential plastic hinges are determined based on the displacement requirement of the structure. A damage index model is used to evaluate the damage of the plastic hinges. Full-scale tests are conducted on two types of shield tunnel lining structures: straight-joint assembly structure (STRJS) and staggered-joint assembly structure (STGJS) under high-water pressure loading conditions. The test results indicate that the assembly method is found to significantly affect the failure pattern, with STRJS and STGJS failing through longitudinal joints and concrete segments, respectively. Furthermore, the STRJS and STGJS exhibit comparable load-bearing capacities, with ultimate loads of 2912 kN and 2867 kN, respectively. The plastic hinge approach is used to compare the failure mechanisms of STRJS and STGJS, revealing that STGJS has fewer joint plastic hinges than STRJS at the ultimate state of the shield tunnel lining structure. The failure of STRJS and STGJS is caused by the joint and segmental plastic hinges exceeding their rotation capacity, respectively. The study highlights the importance of considering the assembly method and the type of plastic hinge in the design of underwater shield tunnel lining structures.